Psychometric evaluation of the Swedish version of the Empathic Experience Scale (EES) - Sarling, Andreas (2024)
Background: This study assessed the factor structure and psychometric properties of the Swedish version of the Empathic Experience Scale (EES), a recently developed scale for empathic traits (Innamorati et al., 2019). According to previous research, EES has two dimensions: Vicarious Experience and Intuitive Understanding. Methods: We used a split-sample method with a combination of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) for an adult population (N = 805) from both Sweden and Finland. Results: Our findings support previous research, favoring a two-factor model over a unidimensional model. The final model provided support for measurement invariance across different grouping variables. Consistent with previous research on empathic traits, women obtained higher scores on both dimensions of the scale compared to men. Furthermore, the EES showed high internal consistency, good discriminant, and convergent validity.